PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD(STUDENT TEAM ACHIEVEMENT DIVISIONS) UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN IPA - Tita Suherni; Nurhamzah CS; Nina Yarana Silmiati (Latifah Pres, 2019)
Applying Cooperative Learning Model Type STAD (Student Team Achievement Divisions) to improve the students learning outcomes in science learning IPA The lack of teachers in the enforcement of the model learning results in low learning outcomes of students,especially in their subjects IPA.Teachers more often use a learning model that conventional and lectures so that less motivated learners the problems that arise is by applying cooperative learning model type STAD can improve the students learning outcomes in science learning in class III MIS Hegarmanah This study aims to improve results learn learners on the study IPA by using a model of learning cooperative type STAD (student team achievement divisions). Methods used in the study this action is the research the class is a observation that implement action in the classroom with using the rules in accordance with the metodologi research conducted in some period or cycle. Based on the results of data processing obtained that the learning outcomes of students on the subjects of IPA has increased significantly after applying cooperative learning model type STAD (student team achievement divisions). It is shown any increase in the value of the average grade in cycle I which 62,69 and has increased significantly in cycle II to 81,78 .thuts it can be said that learning outcomes in cycle II already meet the target. It ca be concluded by using ccoperative learning model type STAD (student team achievement diivisions) can improve the students learning outcomes in the subjects science grade III MIS Hegarmanah.